Prevention of fatigue and insomnia in shift workers—a review of non-pharmacological measures. Issue 1 (December 2016) - Richter, Kneginja; Acker, Jens; Adam, Sophia; Niklewski, Guenter
Abstract Background Excessive fatigue and insomnia are common among shift workers and can lead to negative effects such as reduced work performance, processing errors, accidents at work, absenteeism, reduced quality of life, and symptoms of depression. Moreover, work in rotating shifts can be a risk factor for different somatic and psychiatric diseases and may contribute to poor health, especially in elder adults and women. This review aims to show non-pharmacological preventive measures against fatigue and insomnia in shift workers. Method Computerized literature searches in MedLine and in the Cochrane Library were performed with the following key words: shift work disorder, fatigue, insomnia, shift work, measures, treatment, therapy, strategies and coping. The search was limited to non-pharmacological studies that were conducted on human subjects and published as English-language articles in peer-reviewed journals since 1970. Additional studies were identified through the reference sections of relevant articles. Eighteen articles on fatigue in shift workers, including six original research articles with a total sample size of 3504 probands consisting of industrial workers, office employees, aircraft maintenance engineers, and non-shift workers working in simulated shifts, were analyzed, as well as seven articles on insomnia, including an original research article with a sample size of 26 media workers. Also, 4 reviews on shift work disorder were analyzed. Main The occurrence of fatigue and insomnia in shift workers associated with a working period is described as shift work disorder. Estimations on the prevalence of shift work disorder in shift workers vary between 5 % and about 20 %; about one in three shift workers is affected by insomnia and up to 90 % of shift workers report regular fatigue and sleepiness at the workplace. We concluded that there is a necessity for treatments to improve the sleep quality of the shift working population. The most common non-pharmacological recommendations to improve sleep quality and to reduce insomnia and fatigue were scheduling, bright light exposure, napping, psychoeducation for sleep hygiene, and cognitive-behavioral measures. Conclusion Some important preventive coping strategies for fatigue associated with shift work such as napping and exposure to bright light have already been investigated and are generally approved. A few studies also provide good evidence for the efficacy of cognitive-behavioral techniques in the treatment of chronic primary and comorbid insomnia. These coping strategies summarized in this paper should be considered in the workplace health promotion programs of each work environment to improve working conditions for shift workers and to save money.